Low carbon mobility transitions - Hopkins, D; Higham, J (Goodfellow Publishers, 2016)
The overlapping roles of technological innovation, behaviour change and policy frameworks are critically examined in this book, providing timely insights into the opportunities for decarbonising the current systems of transport, in order to ...